Grid input current feedback active damping control method for IPMSM drives with small DC‐link capacitor. Issue 3 (10th January 2021) - Yin, Quan; Li, Haichun; Luo, Hui; Wang, Qingyi; Miao, Jigui; Hou, Yanting
Abstract: With large input line inductance and low dc‐link capacitance, the small dc‐link drive system shows an instability problem, which is mainly caused by LC resonance between the line side inductor and the dc‐link film capacitor. This paper proposes a grid current feedback active damping control method to improve system stability and suppress the LC resonance. The feedback variables are analyzed, and the detected grid current is selected. Thus, the damping current is consistent with the LC resonance components in grid current, which benefits the drive system power factor and grid current quality. Furthermore, the grid current feedback control loop has been established, and the feedback gain is designed based on system parameters that can be adjusted to fit different systems. The stability margin and robustness of the drive system to the changes in line inductance and dc‐link capacitance are improved. Compared with the conventional voltage‐based damping method, the power factor is increased to 0.984 and the grid current harmonics are reduced to satisfy the requirements of EN61000‐3‐2. The effectiveness of the proposed active damping method is verified by the experimental results.